Sexualidade e ideal de feminilidade: contribuições para o debate - MOREIRA, Ana Cleide Guedes (Círculo Brasileiro de Psicanálise, 2023)
In this article we investigate the relationship between the ideal of femininity, female sexuality and women infection by HIV. Sociocultural ideals are responsible for defining what it is to be feminine and masculine in our culture, conceivingnormality patterns that constitute subjectivity. In the eighteenth century a new femininity modelhas emerged, still in force, whose main author was Jean Jacques Rousseau. In this ideal, women should be passive to men’s desires and needs, would be destined to a single social place - the home - and motherhood, not being able to perform other social functions. In this paper we analyze the problem of HIV infection in women,using the testimony of one of the documentary “Positives” participants. It is necessary to demonstrate the hypothesis that women identified to the mentioned ideal of femininity can not negotiate with their partner the use of the condom in sexual relations, since while submissive to the other person’s desire, they do not place themselves as subjects of their own’s.